Groundwater Exploration for Sustainable Development and Management in a Hard Rock Basin - Deepa Subramani; Pradeep Kamaraj (Applied and Environmental Soil Science)
An attempt was made to use the geoelectrical resistivity method to classify the aquifer zones and ground lithology of the upper Manimuktha sub-basin (a hard rock basin) from the Vellar River in Tamil Nadu. It is more appropriate to compare the electrical conductivity to geophysical resistivity surveys in these areas since the conductivity of the subsurface layer is poor in arid and semiarid regions. A 3 km equal grid was created to use the Schlumberger electrical resistivity method by using the SSR-MP-AT resistivity meter due to its great utility in defining the pattern of subsurface layers (weathered zone and fracture pattern, among others). Forty-eight vertical electrical sounding surveys were performed with a maximum electrode distance of 200 m in different lithologies such as syenite complex (N = 1), garnet-sillimanite-graphite gneiss (N = 1), hornblende biotite gneiss (N = 1), fissile hornblende biotite gneiss (N = 6), and charnockite (N = 39) for sustainable management of groundwater. The thickness and resistivities of subsurface layers were derived from IPI2WIN. Regions with low resistivity and high thickness showed good groundwater potentiality. The results revealed that weathered and fractured formations were favorable for groundwater occurrences. Fourteen types of curves were identified with three-layer, four-layer, and five-layer formations. The “AA” and “AK” types of curves represented the availability of groundwater in appreciable amounts. In addition, the curves associated with the “H” type represented the weathered formation, which is favorable for groundwater occurrences. The high topsoil thickness regions were characterized by potential regions of groundwater. The aquifer thickness showed the most favorable groundwater potential zones in the eastern, small central portion, and it ranged from 12.1 to 192 m. The longitudinal conductance (S) showed good aquifer conditions in the foothills of the northern side and a part of the eastern region. Six resistivity and pseudosection profiles were made in the NW to SE and N to S directions to identify the vertical and lateral variation of groundwater potential. These results were further confirmed by water level data from 48 different locations. It revealed that the excellent groundwater potential was represented towards the eastern direction with a resistivity range of less than 65 ohm.m. This study provides numerous details about groundwater sustainability.